In-situ activated polycation as a multifunctional additive for Li-S batteries. (August 2016) - Chen, Hongwei; Wang, Changhong; Dai, Yafei; Ge, Jun; Lu, Wei; Yang, Jinlong; Chen, Liwei
Abstract: While Li–S batteries are poised to be the next generation high-density energy storage devices, the low sulfur utilization and intrinsic polysulfide shuttle have limited their practical applications. Here, we report that radical polymer Poly(2, 2, 6, 6-tetramethyl-1-piperidinyloxy-4-yl methacrylate) (PTMA)—a stable free radical polymer reported to be potential organic electrode materials–can perform as a multifunctional sulfur-trapping and catalytic binder for high performance Li-S batteries once activated via in-situ electrochemical oxidation. The activated PTMA + not only displays strong binding affinity to polysulfides but also provides PTMA + -assisted additional redox sites and improves the kinetics of the cathode reaction. Thus the novel multifunctional additive for Li-S batteries results in improved cycle life, faster rate performance and most importantly, a significantly increase in specific discharge capacity by ~80%, with specific capacity of 1254 mAh/g and Coulombic efficiency of 96% at a four-hour charge/discharge (C/4) current rate. Graphical abstract: Highlights: In-situ electrochemical activated radical polymer was used as a multifunctional additive for Li-S batteries. The additive not only displays strong binding affinity to polysulfides but also improves the kinetics of the cathode reaction. Significant increase in specific discharge capacity and cycling stability.